A Single-Step Root Coverage Procedure Using Modified Bridge Flap Technique and De-epithelialized Gingival Unit Graft: A Prospective Clinical Study - Neelima Katti; Devapratim Mohanty; Peri Srivani; Humaira Siddiqui; Subash Chandra Raj; Debajani Baral (Wolters Kluwer Medknow Publications, 2024)
Background: The mucogingival conditions associated with the recession defects at the mandibular anterior region, not only make plaque control difficult to be performed by the patient but also pose a problem in passively advancing the tissues at the recipient site. This surgical technique is used to treat multiple recession defects in the mandibular anterior region. Materials and Methods: Twenty-five sites in 17 subjects (11 women and 6 men) underwent modified bridge flap and de-epithelized gingival unit graft (d-GUG) as a single-step treatment modality to cover the denuded root surface, as well as increase the width of keratinized gingiva in recession type 1 gingival recession defects in the mandibular anterior region. Results: Nearly 60% of sites in our study showed complete root coverage, with a mean root coverage percentage of 88.08%. Furthermore, keratinized tissue width, keratinized tissue thickness as well as vestibular depth showed statistically significant increases as compared to baseline levels. Conclusion: Thus, the modified bridge flap technique using d-GUG within the limitations of our study design, showed promising results in terms of recession coverage as well as management of the difficult mucogingival conditions at the mandibular anterior region.